Faktor dan Rencana Aksi Implementasi BCMS Pada Sektor Publik: Studi Kasus Pada Sekretariat Utama BPKP - Bambang Satria A Wibowo; Ancella Anitawati Hermawan (Jurnal Akademi Akuntansi, 2023)
Purpose: Business Continuity Management System (BCMS) is not widely implemented in Indonesian public sector, therefore his study aims to reveal the drivers of BCMS implementation at the public sector and preparation that organization should done for BCMS implementation as required by the ISO 22301:2019 standard.  The object of the study is Chief Secretariat of Badan Pengawasan Keuangan dan Pembangunan (BPKP) which has supporting function for government’s internal audit as BPKP core-business. Methodology/Approach: The research done with case study method with qualitative approach. The primary data in the study was collected through semi-structured interview with people from risk management unit, incidents management unit,  and IT management unit. The data analysis carried out with the benchmarking the drivers of BCMS implementation with previous study and literature and benchmarking the organizaiton existing condition with BCMS requirements. Findings: The study found that there are urgency and need for BCMS implementation in the organization, with the main drivers are informal top-management support, uneven continuity practices, and the increase of organization’s dependency of information technology. Practical and Theoretical Contribution/Originality: Organization need to create the BCMS policy, enhance the competency and awareness about BCMS, and update the incident response procedure as the preparations of BCMS implementation. This research contributing for future public sector implementation of BCMS.